Nødvendigt, tilstrækkeligt, typisk? – nogle tanker om definitionspraksis - Lorentzen, Henrik; Trap-Jensen, Lars (LexicoNordica, 2012)
This paper deals with the general issue of writing good definitions, taking a specific starting point in the principles formulated in the style guide of The Danish Dictionary. After a brief historical survey of definitional practice in selected Danish dictionaries, the paper concentrates partly on the principles and problems of the classical dictionary definition, partly on descriptions of the function and use of words and phrases. Giving their personal view on good and bad definitions based on ideas of prototypicality rather than exhaustiveness and completeness, the authors end by raising the issue of different definitions for different users, drawing on results from a user survey of the online version of The Danish Dictionary.